TINJAUAN EKONOMI ISLAM DALAM BISNIS KARYA SENI KALIGRAFI - FAHRIZA RAMADHAN; Rahmad Syah Putra (Jurnal Ekshis, 2024)
Calligraphy artwork is a work of art that is very popular with the general public, so it often becomes one of the branches of the competition in the Musabaqah Recitations of the Quran, namely the Musabaqah Khatil Qur'an branch. Therefore, not a few make calligraphy a profession and make it a business as a source of livelihood. This study aims to find out the review of Islamic economics in the business of calligraphy artwork. The author uses a descriptive qualitative method in conducting this research, using a literature review approach and conducting interviews with respondents who are resource persons about the calligraphy business world. The results obtained from this study are that Islamic economics does not interfere in how to find wealth, but Islamic economics leaves this matter to humans and recommends seeking wealth with expertise and knowledge. The calligraphy business is one of the jobs that requires expertise and knowledge to run the business, the business of calligraphy artwork is part of producing goods or services through handicrafts which is legally permissible as recommended by Ali Bin Abi Talib to learn calligraphy, because calligraphy is a door of fortune / business opportunities.